Welfare Dynamics in Colombia : Results from Synthetic Panels - Balcazar, Carlos Felipe (World Bank, Washington, DC, 2018)
This study explores the short-run transitions between poverty, vulnerability, and middle class, using synthetic panels constructed from multiple rounds of Colombia's Integrated Household Survey (in Spanish Gran Encuesta Integrada de Hogares). The paper reports results from two approaches to define a vulnerability line: the first one employs a nonparametric and parsimonious model, while the second utilizes a fully parametric regression model with covariates. The estimation results suggest a range of between $8 to $13 per day per person in 2005 purchasing power parity dollars as the vulnerability line. Using an average daily vulnerability line of $10 per day per person, subsequent estimates on welfare dynamics suggest that, during the past decade, 20 percent of the Colombian population experienced downward mobility, and 24 percent experienced upward mobility. Furthermore, upward mobility increases with higher education levels and is lower for female-headed households.